RANCANG BANGUN ALAT PENDETEKSI GAS CO, CO2, DAN SO2 SEBAGAI INFORMASI PENCEMARAN UDARA - Islam, Jilly Haikal; Harianto, Harianto; Wibowo, Madha Christian (Journal JCONES, 2013)
Air pollution is a condition in which the air quality to be damaged and contaminated by substances, both of which are harmless and which endanger the health of the human body. Air pollution usually occurs in big cities as well as dense regions that produce industrial gases containing substances above the acceptable limit. The gases are the main air pollutants are carbon dioxide gas (CO2), carbon monoxide (CO), and sulfur dioxide (SO2). Development of gas detection sensor technology which is currently growing at a rapid pace to provide solutions to overcome the above problems, in this study made ​​a tool to detect gases CO, CO2 and SO2 as air pollution information. This tool can detect the gas content of the air per second so that the gas content of the data obtained and then sent to a computer via wireless communication using the XBee-Pro and saved for later can be processed as air pollution information.